Tuberculosis screening using IGRA and chest computed tomography in patients with inflammatory bowel disease: A retrospective study. Issue 1 (January 2017) - Song, Dong Juan; Tong, Jin Lu; Peng, Jiang Chen; Cai, Chen Wen; Xu, Xi Tao; Zhu, Ming Ming; Ran, Zhi Hua; Zheng, Qing
Abstract : Objectives: To assess the prevalence and potential risk factors of latent tuberculosis infection (LTBI) in Chinese patients with inflammatory bowel disease (IBD) and to evaluate the role of chest computed tomography (CT) in the screening of LTBI. Methods: A single‐center retrospective study was conducted and all IBD patients who had been screened for LTBI by T‐SPOT.TB between December 2011 and January 2016 were enrolled in the study. Both inpatient and outpatient records were collected and comprehensively reviewed. Results: Altogether 534 IBD patients were included. The positivity rate of T‐SPOT.TB was 18.0% overall, 31.9% in IBD unclassified, 22.5% in ulcerative colitis and 13.0% in Crohn's disease patients, respectively. Age, history of TB and the administration of immunosuppressants were significantly associated with T‐SPOT.TB positivity. Among 123 patients who underwent serial testing, the conversion and reversion rate of T‐SPOT.TB was 10.2% and 42.9%, respectively. Furthermore, 102 of 447 (22.8%) patients who underwent chest computed tomography (CT) were found with abnormal CT findings suggestive of LTBI. The concordance rate was 75% between the T‐SPOT.TB and chest CT with a kappa value of 0.25 (95% CI 0.15–0.35). Conclusions: The prevalence of LTBI in IBD patients is high in China. Chest CT is recommended as an alternative to IGRA for screening LTBI of IBD patients before commencing immunosuppressive therapy in high‐prevalence regions.